Not enough to persecute, prevention is the key – The culture of integrity - Klotz, Péter (Public Finance Quarterly, 2025)
Gusztáv Báger: Korrupció: büntetés, integritás, kompetencia. Budapest, Akadémiai Kiadó, 2012